Resolving conflicting cues in processing of ambiguous words: The role of case, word order, and animacy. Issue 8 (August 2020) - Edeleva, Julia; Chrabaszcz, Anna; Demareva, Valeriia
We report results from a self-paced silent-reading study and a self-paced reading-aloud study examining ambiguous forms (heteronyms) of Russian animate and inanimate nouns which are differentiated in speech through word stress, for example, uCHItelja.TEACHER.GEN/ACC.SG and uchiteLJA.TEACHERS.NOM.PL . 1 During reading, the absence of the auditory cue (word stress) to word identification results in morphologically ambiguous forms since both words have the same inflectional marking, -ja . Because word inflection is a reliable cue to syntactic role assignment, the ambiguity affects the level of morphology and of syntactic structure. However, word order constraints and frequency advantage of the GEN over both the NOM and the ACC noun forms with the - a/-ja inflection should pre-empt two different syntactic parses (OVS vs. SVO) when the heteronym is sentence-initial. We inquired into whether the parser is aware of the multi-level ambiguity and whether selected conflicting cues (case, word order, animacy) can prime parallel access to several structural parses. We found that animate and inanimate nouns patterned differently. The difference was consistent across the experiments. Against the backdrop of classical sentence processing dichotomies, the emergent pattern fits with the serial interactive or the parallel modular parser hypothesis.